2006
DOI: 10.1111/j.1365-2842.2006.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness of five different dental ceramic core materials after grinding and polishing

Abstract: In clinical practice, core materials can be exposed after adjustments are made to previously-luted all-ceramic restorations. The purpose of this study was to evaluate the surface roughness of five different dental ceramic core materials after grinding and polishing. Five different ceramic core materials, Vita In-Ceram Alumina, Vita In-Ceram Zirconia, IPS Empress 2, Procera AllCeram, and Denzir were evaluated. Vita Mark II was used as a reference material. The surface roughness, Ra value (mum), was registered u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 15 publications
(32 reference statements)
7
42
2
5
Order By: Relevance
“…Clinically, the kits tested in this study enhanced acceptable polished surfaces, even with statistically significant difference between GP1 and GP2. Furthermore, the values were lower than those found by Kou (0.7 μm) using sof-lex disks (3M, USA) [18] and Lawson (1.1 μm) using the Dialite ZR kit (Brasseler, USA) [7].…”
Section: Discussioncontrasting
confidence: 66%
“…Clinically, the kits tested in this study enhanced acceptable polished surfaces, even with statistically significant difference between GP1 and GP2. Furthermore, the values were lower than those found by Kou (0.7 μm) using sof-lex disks (3M, USA) [18] and Lawson (1.1 μm) using the Dialite ZR kit (Brasseler, USA) [7].…”
Section: Discussioncontrasting
confidence: 66%
“…Although the main indication for polishing discs, which are commonly used in dental clinics, is finishing and polishing dental composite resins, the best polishing results for several types of porcelain were also achieved using the SofLex system in earlier studies. [37][38][39] Furthermore, it was reported that only flat and convex surfaces can be ef- fectively polished with flexible polishing discs such as the Sof-Lex system. 39 Therefore, based on the findings of the present study, polishing discs seem to be effective for polishing porcelain surfaces after orthodontic appliances have been removed.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Furthermore, it was reported that only flat and convex surfaces can be ef- fectively polished with flexible polishing discs such as the Sof-Lex system. 39 Therefore, based on the findings of the present study, polishing discs seem to be effective for polishing porcelain surfaces after orthodontic appliances have been removed.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Sof-Lex discs have also been described as an efficient polishing method for dental ceramics: [11][12] Depending on the ceramic material used and the profilometrical measuring parameters, Ra values ranging from 0.2 µm to 0.7 µm have been achieved. [13][14][15] Furthermore, there are studies indicating that polished surfaces are qualitatively inferior to glazed ones, while other authors describe polished and glazed surfaces as being equivalent in surface roughness. 10,13,[16][17][18][19][20] In summary, results concerning polishing systems and their performance are inconsistent, because of different measuring parameters and different combinations of polishing method and ceramic material.…”
Section: Introductionmentioning
confidence: 99%